Carnosine and diabetic nephropathy - Peters, Verena; Yard, Benito A.; Schmitt, Claus P. (Current medicinal chemistry, 2020)
Diabetic Nephropathy (DN) is a major complication in patients with type 1 or type 2 diabetes - and represents the leading cause of end-stage renal disease. N...